Perlindungan Program Jaminan Sosial Ketenagakerjaan bagi Pekerja Bukan Penerima Upah - Tsabitah, Annisa Farras; Hoesin, H. Siti Hajati (LPPM Institut Pendidikan Nusantara Global, 2024)
Non-wage workers are also included in the informal sector workers and are entitled to social security protection which is carried out in stages in accordance with one of the principles of social security, namely that participation is mandatory. As is known, the development of informal sector workers, especially after the Covid 19 pandemic, has grown very rapidly over time, in the fields of culinary, crafts, household equipment, animals, etc. So the purpose of this article is to discuss employment social security protection for non-wage earners as regulated in Law no. 24 of 2011 concerning Social Security Administering Bodies. Using doctrinal research methods, this article finds that there is a lack of optimization in the absorption of participants in the labor social security protection program by the Employment Social Security Administering Agency due to constraints on the age limit for workers, a lack of understanding by workers in the informal sector of the importance of employment social security and the benefits that can be obtained. accepted. So in this article the ideal social security protection is formulated, namely carrying out comprehensive and gradual socialization by the Employment Social Security Administering Body, the government's role in adjusting the age limits for informal sector workers so that they can provide maximum social security protection, as well as the public's willingness to receive benefits. provided by the Employment Social Security Administering Agency, so that there is synergy and achievement of community welfare.